Two new species of Gerronema (Agaricales, Basidiomycota) from Kerala State, India - Latha, K. P. Deepna; Nanu, Salna; Sharafudheen, Shahina A.; Manimohan, Patinjareveettil (Phytotaxa, 2018)
Gerronema kuruvense sp. nov. and G. keralense sp. nov. are described from Kerala State, India, in the light of both morphology and molecular phylogenetic analysis. Comprehensive descriptions, photographs of both the basidiomes and the micro-structures, and comparisons with morphologically similar and phylogenetically related species are provided. Both morphology and nrITS-rDNA sequence-based molecular phylogenetic analysis proved the novelty of the species and their placement in the genus Gerronema. Both the species were collected from highland riverine islets.